Power spectral analysis of heart rate variability in Bangladeshi healthy male and female (Bangladesh Medical Journal, 2016)
Heart rate variability (HRV) has been considered as an indicator of autonomic nerve function status. We aimed to find out the reference values of heart rate variability by power spectral analysis in our healthy population of both sex. This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka from the period of July 2012 to June 2013. For this, 180 subjects were selected with the age ranging from 15-60 years. All the study subjects were divided into 3 different groups according to age (Group A: 15-30 years; Group B: 31-45 years; Group C: 46-60 years). Each group contained 60 subjects of which 30 were male and 30 were female. Analysis of HRV parameters were done in Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. Systolic blood pressure, diastolic blood pressure, low frequency normalized unit, low frequency / high frequency ratio were significantly higher in male than female. Again high frequency power, high frequency normalized unit were significantly higher in female than male of same age group. This study concludes that male showed higher cardiac sympathetic activities while female showed higher cardiac parasympathetic activities in different age groups.Bangladesh Med J. 2014 Sep; 43 (3): 146-150